Lifestyle and Experience: brand aspects in the view of the users - Scharf, Edson Roberto (Review of Business Management, 2011)
The traditional marketing does not reflect the complexity of the modern consumer, being necessary to add experiential value to the customer. The concept of experiential marketing was the motivator in this study. The main objective of this study is to investigate the experience provided by a particular brand with the participants of a formal association called PHD (Owners of Harley-Davidson), in the state of Santa Catarina. With descriptive character, the research has adopted an online questionnaire based on issues raised by Schouten and McAlexander (1995): the influence on the purchase, the importance of specific attributes as well as the brand living style. The results have pointed to the understanding that the brand provides a hybrid experience, based largely on the identification and sensory dimensions. In conclusion, consumers of Harley-Davidson ";live"; the lifestyle through the experiences that the brand and the use of its products provide, specifically the sponsored events and the sound of the engine. Contrary to the literature, however, tattoos and movies have little importance to experience the lifestyle of Harley-Davidson. Key words: Marketing. Experiential marketing. Experience. Harley-Davidson lifestyle. Sustainable competitive advantage.